From nonperson to public intellectual: The life and works of Yu Jianrong: Guest editors' introduction - Pils, Eva; Svensson, Marina (Contemporary Chinese Thought, 2014)
This special issue focuses on the multifaceted scholar and public intellectual Yu Jianrong. Yu is a sociologist with the Chinese Academy of Social Sciences (CASS), an accomplished scholar on China's social problems, a public intellectual vocal in some of the country's most heated debates, and a blogger with 1.5 million followers on the country's most popular social media platform, Sina Weibo. His impact as a public intellectual has also been noticed abroad, and in 2012, Foreign Policy included him on their list of the world's most influential intellectuals.
CRIS-Team Scopus Importer:2023-03-21